Measurement of air cooling characteristics for the several surface types of Li-Ion battery - Byelyayev, A.A.; Fedorchenko, D.V.; Khazhmuradov, M.A.; Lukhanin, O.A.; Lukhanin, O.A.; Martynov, S.O.; Rudychev, Y. V.; Sporov, E.O.; Rohatgi, U.S. (Вопросы атомной науки и техники, 2013)
The system of air cooling for Li-Ion batteries is considered. Experimental setup included thermal chamber and Li-Ion battery cell simulators with temperature sensors. We investigated static and dynamic cooling regimes for several types of cooling surfaces, for different gaps between the simulators and flow rates. Experimental results are compared to the data of computer modelling using SolidWorks Flow Simulation software. The cooling efficiencies of the various surfaces for static and transient heat emission modes are compared. Розглянуто систему повiтряного охолодження для Li-Ion-батарей. Експериментальна установка включала в себе термокамеру та симулятори чарунок Li-Ion-батареї з датчиками температури. Ми дослiджували статичнi та динамiчнi режими охолодження для декiлькох типiв охолоджуючих поверхонь, для рiзних зазорiв мiж симуляторами та швидкостей потоку. Експериментальнi результати порiвнювалися з даними комп’ютерного моделювання за допомогою програмного забезпечення Solid Works Flow Simulation. Порiвнюються ефективностi охолодження для рiзних поверхонь при статичному i перехiдному режимах тепловидiлення. Рассмотрена система воздушного охлаждения для Li-Ion-батарей. Экспериментальная установка включала в себя термокамеру и симуляторы ячеек Li-Ion-батареи с датчиками температуры. Мы исследовали статические и динамические режимы охлаждения для нескольких типов охлаждающих поверхностей, для различных зазоров между симуляторами и скоростей потока. Экспериментальные результаты сравнивались с данными компьютерного моделирования при помощи программного обеспечения SolidWorks Flow Simulation. Сравниваются эффективности охлаждения для различных поверхностей при статическом и переходных режимах тепловыделения.